Localization and Diagnosis of Short-Circuit Faults in Transformer Windings Injected by Damped Oscillatory Wave - Chengbo Hu; Xueqiong Zhu; Yongling Lu; Ziquan Liu; Zhen Wang; Zhengyu Liu; Kangyong Yin (Energies)
Power transformers, as critical components in regional power distribution and transmission systems, require early fault detection to ensure system reliability. This paper presents a scalable design capable of rapidly simulating winding faults in experimental transformers. By diagnosing three-phase transformer winding short-circuit faults using oscillatory shock voltages and numerical statistical methods, the relationship between the transfer function and winding short-circuit faults is investigated. The experimental results show that winding short-circuit faults cause significant changes in the transfer function curve. By analyzing transfer function variations across different phases, the location of a fault can be effectively determined. Furthermore, the correlation coefficient and absolute logarithmic deviation provide a clear indication of the fault severity. The transfer function of the high-voltage phase-to-phase is particularly sensitive to winding short-circuit faults. In non-fault phases, after the application of damped oscillatory waves, the transfer function correlation coefficient becomes negative and the absolute logarithmic deviation increases linearly with fault severity. These findings provide a rapid diagnostic solution for determining both the faulty phase and the severity of damage in three-phase transformer winding short-circuit faults.